2011
DOI: 10.1074/jbc.m110.209569
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of the Complex Stereoselectivity of Human Butyrylcholinesterase for the Neurotoxic V-agents

Abstract: Nerve agents are chiral organophosphate compounds (OPs) that exert their acute toxicity by phosphorylating the catalytic serine of acetylcholinesterase (AChE). The inhibited cholinesterases can be reactivated using oximes, but a spontaneous timedependent process called aging alters the adduct, leading to resistance toward oxime reactivation. Human butyrylcholinesterase (BChE) functions as a bioscavenger, protecting the cholinergic system against OPs. The stereoselectivity of BChE is an important parameter for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…k i for inhibition of human BChE by potent OP nerve agents are fast; for instance, 1.1 × 10 7 M − 1 · min − 1 for VX S ( − ) [34] and 3.8 × 10 8 M − 1 · min − 1 for cyclohexylsarin [35]. Values of k i and k i for inhibition of BChE by CSP are comparable and are thus among the highest values for reaction of OP agents with ChEs, making CSP one of the most potent irreversible inhibitors of human BChE that is known.…”
Section: Inhibition Of Wt Bche and D70g By Cspmentioning
confidence: 99%
“…k i for inhibition of human BChE by potent OP nerve agents are fast; for instance, 1.1 × 10 7 M − 1 · min − 1 for VX S ( − ) [34] and 3.8 × 10 8 M − 1 · min − 1 for cyclohexylsarin [35]. Values of k i and k i for inhibition of BChE by CSP are comparable and are thus among the highest values for reaction of OP agents with ChEs, making CSP one of the most potent irreversible inhibitors of human BChE that is known.…”
Section: Inhibition Of Wt Bche and D70g By Cspmentioning
confidence: 99%
“…The crystalographic structure PDB file of recombinant human acethylcholinesterase in complex with donepezil (PDB ID: 4EY7 [26]) and the X-ray structure PDB file of human butyrylcholinesterase (PDB ID: 2XQG [27]) were obtained from the RCSB Protein Data Bank (www.pdb.org) (28). One of the monomers in the crystalographic structure of human BChE and all water and ligand molecules besides donepezil were extracted from the PDB files using the PyMOL Molecular Graphics System, Version 1.3 (Schrödinger LLC, New York, NY, USA).…”
Section: Crystalographic Structurementioning
confidence: 99%
“…253 One month after intoxication, mnemonic cognitive performances of the LWL group were similar to controls while the HWL group did not exhibit any learning skill. 253 Three months after poisoning, compared to controls, the LWL group showed similar mnemonic performances in the maze test but a mild deficit in the Morris water maze task. At the same time, learning skills slightly recovered in the HWL group.…”
Section: Neurological and Cognitive Impairmentmentioning
confidence: 81%
“…252 Soman exposure can also impair fear conditioning in rats, with soman-exposed animals spending less time freezing than controls, possibly due to the neuropathy observed in the hippocampus, amygdala, and thalamus. 253 Filliat and colleagues found that mice exposed to 1.2 LD50 of soman (110 mg/kg in 200 ml of saline solution) could be divided into high-weight loss (HWL) and low-weight loss (LWL) groups, and that this grouping was predictive of neuropathological damage to the hippocampus. 254 Initially, both groups of mice showed a decrease in their motor performance subsequent to an acute soman toxicity phase.…”
Section: Neurological and Cognitive Impairmentmentioning
confidence: 99%